Improving students' critical thinking skills using e-modules-contextual teaching and learning (CTL) on the interaction of living organisms with their environment - Amrilizia, Nassa; Habiddin, Habiddin; Marsuki, Muhammad Fajar (Journal of Disruptive Learning Innovation (JODLI), 2022)
The ability to think critically is one of the 21st-century skills that students should master. Previous studies and international surveys such as PISA showed that the profile of Indonesian students' critical thinking skills is insufficient. This study developed e-modules based on Contextual Teaching and Learning (CTL) on the interaction of living organisms with their environment. The e-module was declared very feasible regarding its content, technological and assessment tools with 86.92%, 86.33%, and 93.5%, respectively. The readability test results by teachers and students were categorised as very feasible with 89,66 % and 88.08% percentages. The e-module was also tested empirically and demonstrated an improvement in students' understanding of the topic. The statistical procedures confirmed it, including the paired-sample t-test and the N-gain analysis.